PENERIMAAN RETRIBUSI IZIN GANGGUAN (HO) DI KECAMATAN TAMPAN KOTA PEKANBARU TAHUN 2012 – 2014 - Intan Andriyani Putri; Ishak " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This study aims to determine the cause of the decline in retribution permit interference, especially in the city of Pekanbaru, especially in the District Charming. The number of businesses which do not deal with this permit, both new and renewal becomes impairment of retribution permit the interruption disampaing other problems. This study uses the theory of authority (authority) and qualitative research methods with data analysis desktriptif. This study shows that first, the decline retribution permit interference in District Charming terms of public response due to low participation and awareness in the processing of business permits that include permission interference. Second, the behavior of bureaucratic apparatus which is less responsive and accountable is also a problem that retribution menurun.Ketiga nuisance permit, the Government in both political authority, control and enforcement is not working optimally and impressed not only focus on the business license with large-scale disturbances.Keywords: Policies, Licensing, levies, Authority